Intracardiac MR imaging (ICMRI) guiding‐sheath with amplified expandable‐tip imaging and MR‐tracking for navigation and arrythmia ablation monitoring: Swine testing at 1.5 and 3T. Issue 6 (10th February 2022) - Schmidt, Ehud J.; Olson, Gregory; Tokuda, Junichi; Alipour, Akbar; Watkins, Ronald D.; Meyer, Eric M.; Elahi, Hassan; Stevenson, William G.; Schweitzer, Jeffrey; Dumoulin, Charles L.; Johnson, Thomas; Kolandaivelu, Aravindan; et al.
Abstract : Purpose: Develop a deflectable intracardiac MR imaging (ICMRI) guiding‐sheath to accelerate imaging during MR‐guided electrophysiological (EP) interventions for radiofrequency (500 kHz) ablation (RFA) of arrythmia. Requirements include imaging at three to five times surface‐coil SNR in cardiac chambers, vascular insertion, steerable‐active‐navigation into cardiac chambers, operation with ablation catheters, and safe levels of MR‐induced heating. Methods: ICMRI's 6 mm outer‐diameter (OD) metallic‐braided shaft had a 2.6 mm OD internal lumen for ablation‐catheter insertion. Miniature‐Baluns (MBaluns) on ICMRI's 1 m shaft reduced body‐coil‐induced heating. Distal section was a folded "star"‐shaped imaging‐coil mounted on an expandable frame, with an integrated miniature low‐noise‐amplifier overcoming cable losses. A handle‐activated movable‐shaft expanded imaging‐coil to 35 mm OD for imaging within cardiac‐chambers. Four MR‐tracking micro‐coils enabled navigation and motion‐compensation, assuming a tetrahedron‐shape when expanded. A second handle‐lever enabled distal‐tip deflection. ICMRI with a protruding deflectable EP catheter were used for MR‐tracked navigation and RFA using a dedicated 3D‐slicer user‐interface. ICMRI was tested at 3T and 1.5T in swine to evaluate (a) heating, (b) cardiac‐chamber access, (c) imaging field‐of‐view and SNR, and (d) intraprocedural RFA lesion monitoring. Results: The 3T and 1.5T imaging SNR demonstrated >400% SNR boost over a 4 × 4 × 4 cm 3 FOV in the heart, relative to body and spine arrays. ICMRI with MBaluns met ASTM/IEC heating limits during navigation. Tip‐deflection allowed navigating ICMRI and EP catheter into atria and ventricles. Acute‐lesion long‐inversion‐time‐T1‐weighted 3D‐imaging (TWILITE) ablation‐monitoring using ICMRI required 5:30 min, half the time needed with surface arrays alone. Conclusion: ICMRI assisted EP‐catheter navigation to difficult targets and accelerated RFA monitoring.